2010
DOI: 10.1007/978-3-642-15763-9_4
|View full text |Cite
|
Sign up to set email alerts
|

Transactions as the Foundation of a Memory Consistency Model

Abstract: We argue for transactions as the synchronization primitive of an ordering-based memory consistency model. Rather than define transactions in terms of locks, our model defines locks, conditions, and atomic/volatile variables in terms of transactions. A traditional critical section, in particular, is a region of code, bracketed by transactions, in which certain data have been privatized. Our memory model, originally published at OPODIS'08, is based on the database notion of strict serializability (SS). In an exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
2
2

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…Some researchers have argued that despite these benefits, strong atomicity is not worth its costs in existing STMs [12,14]. By providing strong atomicity naturally at low cost, this paper's STM offers a new data point to consider in the tradeoff between performance and semantics.…”
Section: Transactional Semanticsmentioning
confidence: 99%
“…Some researchers have argued that despite these benefits, strong atomicity is not worth its costs in existing STMs [12,14]. By providing strong atomicity naturally at low cost, this paper's STM offers a new data point to consider in the tradeoff between performance and semantics.…”
Section: Transactional Semanticsmentioning
confidence: 99%
“…Dalessandro et al [2010b] have observed that privatization is semantically equivalent to locking-it renders a shared object temporarily private. e canonical example of privatization arises with shared containers through which threads pass objects to one another.…”
Section: E Privatization Problemmentioning
confidence: 99%
“…(Also: perlocation timestamps aren't privatization safe [16].) As an alternative to opacity, an STM system may sandbox inconsistent transactions by performing validation immediately before any "dangerous" instruction, rather than after every load [5], but for safety in the general case, a very large number of validations may still be required.…”
Section: How Do We Validate?mentioning
confidence: 98%